Insecticide Resistance Development in Aedes aegypti upon Selection Pressure with Malathion - Hidayati, H.; Nazni, W.A.; Lee, H.L.; Sofian-Azirun, Mohd (Malaysian Society of Parasitology and Tropical Medicine, 2011)
Bioassay test against malathion had been carried out with larval and adult stages of Aedes aegypti. The mosquitoes were under selection pressure against malathion for fortyfive consecutive generations. The rate of resistance development was measured by LC 50 and LT 50 values. The larvae and adult females, after subjection to malathion selection for 45 generations, developed high resistance level to malathion, with resistance ratio of 52.7 and 3.24 folds, respectively over control mosquitoes. Cross-resistance towards the same and different groups of insecticides was determined using the F44 and F45 malathion-selected adult females. Insecticides tested were DDT (4.0), permethrin (0.75), propoxur (0.1), fenitrothion (1), Î»-cyhalothrin (0.05) and cyfluthrin (0.15). Results indicated that the mosquitoes were highly resistant to DDT and fenitrothion, moderately resistant to propoxur, tolerant to permethrin and Î»-cyhalothrin, and very low resistant to cyfluthrin.